A cluster of lung injury cases associated with home humidifier use: an epidemiological investigation. Issue 8 (31st January 2014) - Kim, Hwa Jung; Lee, Moo-Song; Hong, Sang-Bum; Huh, Jin Won; Do, Kyung-Hyun; Jang, Se Jin; Lim, Chae-Man; Chae, Eun Jin; Lee, Hanyi; Jung, Miran; Park, Young-Joon; Park, Ji-Hyuk; et al.
Abstract : Background: In April 2011 a tertiary hospital in Seoul, Korea reported several cases of severe respiratory distress of unknown origin in young adults. Methods: To find the route of transmission, causative agent and patient risk factors of the outbreak, an investigation of the epidemic was initiated. Clinicopathological conferences led to the suspicion that the cases related to an inhalation injury. An age- and sex-matched case–control study was therefore performed to examine the inhalation exposure of the patients to various agents. Results: Of the 28 confirmed cases, 18 agreed to participate. A total of 121 age- and sex-matched controls with pulmonary, allergic or obstetric disease were selected. All patients and controls completed questionnaires with questions about exposure to various inhalants. The crude ORs for patient exposure to indoor mould, humidifier use, humidifier detergent use and insecticide use were 4.4 (95% CI 1.5 to 13.1), 13.7 (95% CI 1.8 to 106.3), 47.3 (95% CI 6.1 to 369.7) and 3.9 (95% CI 1.3 to 11.7), respectively. However, when considered concurrently, indoor mould and insecticide use lost statistical significance. Moreover, humidifier use was ruled out as the cause because of a lack of biological plausibility and the weak strength of the association. This suggested that humidifier disinfectant was the cause of the outbreak. This information led the Korean government to order the removal of humidifier detergents from the market. In the years following the ban, no additional cases were detected. Conclusions: Epidemiological evidence strongly suggests that the lung injury outbreak was caused by humidifier detergent use at home.